(untitled) (European Journal of Pure and Applied Mathematics, 2018)
Let R be a semiprime ring. A mapping F : RÂ â†’Â R (not necessarily additive) is called a multiplicative (generalized) reverse derivation if there exists a mapÂ Â d : RÂ â†’ R (not necessarily a derivation nor an additive map) such that F(xy) = F(y)x + yd(x) for all x, yÂ Ñ” R. In this paper we investigate some identities involving multiplicative (generalized) reverse derivation and prove some theorems in which we characterize these mappings.